Multimodality Imaging of Subclinical Aortic Atherosclerosis: Relation of Aortic Stiffness to Calcification and Plaque in Female Twins - Cecelja, Marina; Hussain, Tarique; Greil, Gerald; Botnar, Rene; Preston, Rebecca; Moayyeri, Alireza; Spector, Tim D.; Chowienczyk, Philip (Hypertension (Dallas, Tex. 1979), 2013)
Aortic stiffness, an important predictor of cardiovascular events, may relate to aortic calcification rather than noncalcified atherosclerotic plaque. The aim of this study was to determine the relation of aortic stiffness to aortic plaque and aortic calcification in asymptomatic postmenopausal women. One hundred female twins (mean age±standard deviation 64±7 years) underwent computed tomography and magnetic resonance imaging (black-blood sequence) of the aorta. The topographical relation of plaque on magnetic resonance images and calcification on computed tomography images was assessed on magnetic resonance/computed tomography fused images. Carotid–femoral pulse wave velocity was used as a measure of aortic stiffness. Aortic plaque was identified in 87% and calcification in 65% of subjects, both increased with age and were higher in the abdominal compared with thoracic aorta (P<0.0001). Plaque correlated with calcification (R=0.68; P<0.0001), but was also detected in 58% of women who had no calcification. Pulse wave velocity (adjusted for age and blood pressure) increased across quartiles of calcification (P<0.01) but not plaque score (P=0.56). Shared genetic factors accounted for >99% of the correlation (0.35) between PWV and calcification. In conclusion, there is a high prevalence of subclinical atherosclerosis within the aorta in asymptomatic middle-aged women. Aortic stiffening relates to aortic calcification, but not to atherosclerotic plaque burden, and the association of aortic stiffness with calcification is driven by common genes.